Analisis Faktor Risiko Kecelakaan Kerja pada Tenaga Kerja Produksi PT Indotama Omicron Kahar di Purworejo, Jawa Tengah - Disca Pravitra; Tuntas Bagyono; Lilik Hendrarini (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Work accident is an incident that is undesired by labors. Prevention of accident needs to be im-plemented by means of analyzing the risk factors, such as the use of PPE and work behavior, as well as the equipment factors, e.g. tools layout and machine safety. The purpose of this research was to understand the risk factors of work accident among production labors in the stripping section of PT Indotama Omicron Kahar in Purworejo, Central Java, by conducting a cross secti-onal survey. The study sample was all 104 labors in that section. The study results were ana-lyzed descriptively in tabulation and analytically by using Pearson correlation test with 95 % sig-nificance level. The conclusions of this research shows that: there is a relationship between PPE using and work accident (p-value < 0,001); there is a relationship between work behavior and work accident (p-value = 0,003; there is a relationship between the layout of the tool and work accident (p-value < 0,001); and work tools which were not equipped by security mecha-nism, has 67,3 % accident or were experienced by 70 respondents. The management of the industry is advised: to give guidance to their workers about the importance of PPE using while they doing their job; to evaluate the layout of production machines and tools; as well as to equip them with safety features.